Legasi Akatthinai dalam lirik lagu Tamil gubahan Vaali - Palani Krishnasamy (2018)
This study aims to identify the elements of Akamtthinai, analyze the legacy ofAkatthinai and assess the highlights of Akam literature influence found in Tamil song lyricscomposed by Vaali, featured in Vaali 1000 Tamil song anthology. This study uses qualitativeapproach based on the library method and text analysis method. The Theory of Akatthinai pioneeredby Tholkaappiyar was used to carry out this study. The findings show that there are 673 ofthe 1000 songs composed by Vaali have the elements of Akatthinai. Of the total, 279 songs were composed based on Kurinjitthinai, 161 songs composed based onMullaitthinai, 132 songs composed based on Maruthatthinai, 58 songs composed based onNeythalthinai and 44 songs composed based on Paalaitthinai. The findings also show Vaali'sability to include the influence of Akam literature in its quotes. This study proves thatTamil song lyrics composed by Vaali have high level of Akam literary value. The implications ofthisstudy will be a guide to future Tamil songwriters to improve their composition.